Analisis Kelayakan Buku Teks Bahasa Indonesia Kelas II SD Berdasarkan Aspek Isi, Penyajian, Bahasa, dan Grafik - Luthfia Nur Afifah; Anggi Fitri Hasanah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Textbooks are the heart of the learning process, therefore an in-depth analysis of the suitability, relevance, and pedagogical potential of textbooks is crucial to ensure that learning outcomes can be achieved optimally. This study aims to analyze and describe based on aspects of content, presentation, language, graphics in the Indonesian language textbook for grade II elementary school revised independent curriculum published by Erlangga by Dr.A. Indradi, M.Pd & Rahmah Purwahida, S.Pd., M.Hum. The method used is qualitative descriptive analysis by referring to textbook feasibility guidelines. The results of the analysis show that this textbook is generally suitable for use. The suitability of the material with learning outcomes includes the development of four language skills, namely listening, speaking, reading, and writing, which are presented in an integrated and contextual manner. The presentation of the material is considered effective through the use of simple language, logical flow, and varied assignments. Overall, this textbook is a relevant and supportive learning resource in implementing the independent curriculum at the grade II elementary school level.